From Early All Stars History: A Bombshell: 1940 Hell Yard Record: The First Ever - Rennie, Bukka (Sunday Express)
It has been uncovered that the earliest known recording of a steel band was the 1940 Hell Yard recording of a calypso "Lion Oh" performed by the Roaring Lion.
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago -- History; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago -- History